2021
DOI: 10.1177/10781552211037993
|View full text |Cite
|
Sign up to set email alerts
|

Novel agents for myelodysplastic syndromes

Abstract: Review objective There have been several advances in the field of myelodysplastic syndromes over the past year, yielding two new US Food and Drug Administration drug approvals. The pharmacology, pharmacokinetics, clinical trials, therapeutic use, adverse effects, clinical use controversies, product description, and upcoming trials for myelodysplastic syndromes novel agents luspatercept-aamt and decitabine/cedazuridine are reviewed. Data sources This review article utilized primary information obtained from bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…5-Aza-dC has been clinically used under the name decitabine. The efficacy of DNA methylation inhibitor decitabine plus the cytidine deaminase inhibitor cedazuridine in the treatment of MDS and chronic myelomonocytic leukemia was demonstrated in the recent clinical studies of ASTX727-01-B and ASTX727-02 and they were approved by the United States Food and Drug Administration [ 3 , 4 , 5 ]. The ASTX727-01-B study showed that 18% that were in complete remission and 49% of patients were free from transfusion dependence, and the ASTX727-02 study showed that 21%that were in complete remission and 53% of patients were free from transfusion dependence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5-Aza-dC has been clinically used under the name decitabine. The efficacy of DNA methylation inhibitor decitabine plus the cytidine deaminase inhibitor cedazuridine in the treatment of MDS and chronic myelomonocytic leukemia was demonstrated in the recent clinical studies of ASTX727-01-B and ASTX727-02 and they were approved by the United States Food and Drug Administration [ 3 , 4 , 5 ]. The ASTX727-01-B study showed that 18% that were in complete remission and 49% of patients were free from transfusion dependence, and the ASTX727-02 study showed that 21%that were in complete remission and 53% of patients were free from transfusion dependence.…”
Section: Discussionmentioning
confidence: 99%
“…The ASTX727-01-B study showed that 18% that were in complete remission and 49% of patients were free from transfusion dependence, and the ASTX727-02 study showed that 21%that were in complete remission and 53% of patients were free from transfusion dependence. The ASTX727-02 trial showed that 21% that were in complete remission and 53% of patients were free from transfusion dependency [ 3 , 4 , 5 ]. These data suggest that the improvement of therapeutic strategy is still necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation